Immature stages of the genus Ectemnostega Enderlein (Hemiptera: Heteroptera: Corixidae), with an identification key to instars and redescription of the nymphs of E. (Ectemnostega) quadrata (Signoret) - Konopko, Susana Amanda (2013)
The egg and the five instars of Ectemnostega are described based on examined material and published information. The characters most useful in identifying nymphs of Ectemnostega are body and head lengths and widths; number of transverse sulcations of the rostrum; chaetotaxy of mesofemur, meso- and metatibiae, metatarsus, and pterothorax; and grade of development of wing pads. A key to the five nymphal instars of Ectemnostega is provided. The egg of E. quadrata is figured and described for the first time; and the five instars are redescribed in detail and illustrated, with emphasis on the morphometry and chaetotaxy of selected structures.